Observation of wrinkle induced potential drops in biased chemically derived graphene thin film networks - Ladak, S; Ball, J; Moseley, D; Eda, G; Branford, W; Chhowalla, M; Anthopoulos, T; Cohen, L (2013)
Graphene-based electronics show much promise due to the potential high charge-carrier mobility of the material as well as its flexibility in preparation on different substrates. Recently there has been much evidence suggesting that the wrinkle structures found in pristine graphene inhibit electron transport, reducing device performance. In this study the inhibiting role of standing wrinkles within chemically derived graphene are studied quantitatively using Kelvin force microscopy. Samples were evaluated before and after annealing at 250 C to observe changes in the channel's surface potential dependence on the state of reduction. Annealed samples were found to have inter-flake and intra-flake contribution to the potential drop and that for the latter a correlation between the potential drop magnitude and wrinkle density is found, although there is no correlation with wrinkle height. Statistical averaging across many images demonstrated that the average lower limit of wrinkle resistance in these devices is approximately 4.5 kΩ. Such high resistance demonstrate definitively that elimination of wrinkles within graphene oxide based devices is essential in order to obtain optimum performance. © 2013 Elsevier Ltd. All rights reserved.